Healthcare costs among patients with dementia‐related psychosis: Comparing dementia with Lewy bodies with other dementias: Developing topics. (7th December 2020) - Abler, Victor; Rashid, Nazia; Skoog, Ben; Halpern, Rachel; Bunner, Scott; Frazer, Monica S
Abstract: Background: DLB is the second‐most common form of degenerative dementia and it's unclear whether healthcare costs differ for patients with DLB and Alzheimer's disease. [1], [2]. The differential presentation of psychosis among dementias[3] may affect healthcare costs. [1] Bostrom F, Jonsson L, Minthon L, Londos E. Patients with Lewy body dementia use more resources than those with Alzheimer's disease. Int J Geriatr Psychiatry 2007;22(8):713‐719. [2] Zhu CW, Scarmeas N, Stavitsky D, Albert M, Brandt J, Blacker D, Sano M, Stern Y. Comparison of costs of care between patients with Alzheimer's disease and dementia with Lewy Bodies, Alzheimer's Dementia, July 2008; 4(4):280‐284. [3] Tzeng R, Tsai C, Wang C, Wang T, Chiu P. Delusions in patients with dementia with Lewy bodies and the associated factors. Behavioural Neurology, 2018:1‐8. Method: This claims data analysis examined commercial and Medicare Advantage with Part D (MAPD) enrollees aged ≥40 years with evidence of psychosis (antipsychotic (AP) treatment lasting ≥45 days or ≥1 AP pharmacy fill+≥1 psychosis diagnosis) and ≥2 diagnoses for the same type of dementia from 01Jun2016–31May2018. The earliest AP fill was the index date. Continuous insurance enrollment was required for 12 months before and after index. DRP and DLB patients were matched 1:1. Patient characteristics and healthcare costs were analyzed descriptively. Result: Matched DLB and DRP cohorts (n=442 each) had average age of 78.3 years, were 53.6% male, and 89.8% had MAPD coverage. 44% of DRP patients had ≥2 Alzheimer's diagnoses and 32% had ≥2 unspecified dementia diagnoses. DLB patients had a significant pre‐index to post‐index increase for total all‐cause healthcare costs (from $5, 392 to $8, 046, p<0.01) while pre/post differences among DRP patients were not significant. DLB patients had significantly higher mean post‐index pharmacy costs for all‐cause ($6, 616 vs. $4, 515), dementia‐related ($810 vs. $675) and psychosis‐related ($2, 344 vs. $623) medications, and higher mean psychosis‐related total healthcare costs ($5, 801 vs. $2, 687) than DRP. Conclusion: DLB patients had higher medication and psychosis‐related costs than DRP patients who had other dementias.